Distribución espacio temporal de insectos acuáticos en quebradas de la cuenca media del Río Nanay y eje carretero Iquitos - Nauta, Loreto – Perú - Chunga Mozombite, Ludie Andrea (2022)
In the present study, the spatial and temporal distribution of aquatic insects was analyzed in 10 streams located between the middle basin of the Nanay River (Zone 1: San Pedro, Santa Cruz, Tambishi, Agua Negra and Llanchama) and the area of influence of the highway axis. Iquitos-Nauta (Zone 2: Habanillo, Lindero, Pintuyacu, Tocón and Paujil); in three collection periods: emptying mean, emptying and growing mean, Loreto, Peru - 2019. A total wealth of 63 families was reported, distributed in 10 orders (Ephemeroptera, Odonata, Plecoptera, Blattodea, Megaloptera, Hemiptera, Coleoptera, Trichoptera, Lepidoptera and Diptera) and an abundance of 4,771 individuals; where Chironomidae was the most representative family, with 1,826 (38.27%) individuals reported. The results of spatial distribution show that there are significant differences between the collections of Zone 1 and 2 (p = 0.01), reporting greater richness (54 families), abundance (3,218 individuals) and diversity (H = 2.26) in streams of the Zone 2; while the highest dominance (D = 0.33) is reported in streams of Zone 1. Regarding the temporal distribution, significant differences are reported between the 3 evaluated collection periods (p = 0.035), being the emptying period where the registers the greatest wealth (45 families), abundance (1531 individuals) and diversity (H = 2.33); while the greatest dominance is registered in the emptying mean (D = 0.31) and the increasing mean (D = 0.25). This study reveals that the richness, abundance, diversity and dominance of aquatic insects in the streams of this study is influenced by the different anthropogenic incidence, access route and type of stream that characterizes the two collection areas; as well as by the periods of variation of the water level of the rivers of the Amazonian plain.